2014
DOI: 10.1007/s40336-014-0079-6
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of SPECT imaging in pulmonary embolism

Abstract: Outcome studies have shown that pulmonary embolism can be safely excluded in patients with negative ventilation/perfusion (V/Q) single-photon emission computed tomography (SPECT). The effective radiation dose of V/Q SPECT is much less than with computed tomographic (CT) pulmonary angiography, which would make it preferable to CT angiography in many young female patients. The accuracy of V/Q SPECT, however, is difficult to assess, because most published investigations are limited by incorporation bias or partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…41 However, they have incorporated into the meta-analysis studies judged as having a high risk of bias, especially studies with an incorporation bias. 44 Surprisingly, although V/Q SPECT has been widely adopted in nuclear medicine departments in daily clinical practice, no management outcome study or clinical trial has been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 However, they have incorporated into the meta-analysis studies judged as having a high risk of bias, especially studies with an incorporation bias. 44 Surprisingly, although V/Q SPECT has been widely adopted in nuclear medicine departments in daily clinical practice, no management outcome study or clinical trial has been published.…”
Section: Discussionmentioning
confidence: 99%
“…A few systematic reviews and meta‐analyses on the diagnostic accuracy of V/Q SPECT have been published 41‐43 and concluded that V/Q SPECT was superior to planar imaging 41 and superior 43 or equal to CTPA 41 . However, they have incorporated into the meta‐analysis studies judged as having a high risk of bias, especially studies with an incorporation bias 44 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, V/Q SPECT has not achieved the same standard of validation as others diagnostic tests including planar V/Q imaging (1,6-9), CTPA (28-30), or D-dimer testing (31,32), which may impede its widespread acceptance by clinicians. Indeed, although there is an extensive literature reporting the superior diagnostic performances of V/Q SPECT as compared with V/Q planar, the exact accuracy of V/Q SPECT for PE diagnosis is still unknown (20,23). Most importantly, although all diagnostic tests and strategies (including CTPA, planar V/Q, or Ddimer) for PE diagnosis have been validated in large management outcome studies, such a study with V/Q SPECT is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Although V/Q SPECT has many proponents within the nuclear medicine community, publications from nonnuclear medicine specialists often still focus on planar imaging, in particular referring to its high rate of nondiagnostic examinations (21,22). Some have described V/Q SPECT as a new technology requiring definitive validation (10,23). Indeed, a large management outcome study based on the V/Q SPECT for PE diagnosis is lacking.…”
mentioning
confidence: 99%